An investigation of the possibilities of finding adequate techniques of therapy for use in cases of stealing-behaviour in children - De Kock, David Faure (Department of Psychology, 2023)
Aim: To investigate the problem of stealing-behaviour in children with a view to developing a system of therapy based on the laws of learning as presented by Clark Hull. The nature of the problem: Stealing behaviour in the child is considered to be a symptom of some underlying causal condition. Such a general statement means nothing unless it can be expanded to answer the questions: 1) How is stealing selected from the many possible responses. 2) How does liltealing become established as a response to the particular causal situation. This paper will attempt to find an answer to these questions by considering stealing cases treated at the Child Guidance Clinic of the University of Cape Town and an attempt will be made to indicate suitable methods of therapy.